Some reflections on the concept of 'development' - Aram Ziai (University of Bonn, Center for Development Research (ZEF), 2011)
From a poststructuralist perspective tracing the relation between words and meanings, the paper discusses the implicit assumptions of the concept of 'development'. It argues that the concept has Eurocentric, depoliticising and authoritarian implications which can not easily be eliminated by simply redefining it in a progressive manner. The paper also explores the productive misunderstandings arising from the different definitions of 'development' and the potential alternative concepts development researchers might be using instead.
Keywords: 330; Development theory; discourse analysis; poststructuralism